Redesain Dan Pengembangan Website Pondok Pesantren Uzlifatil Jannah Untuk Meningkatkan Efisiensi Penyampaian Informasi - Ibnu Adhan, Alvito; Anshari, Muhammad; Hilal Dzakwan, Muhammad; Al Islami, Hidayatullah (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2025)
The educational establishment Pondok Pesantren Uzlifatil Jannah has been in operation since 2015. The need for a medium to spread information more widely has grown over time. In order to facilitate more efficient information distribution, Pondok Pesantren Uzlifatil Jannah's official website was created in 2023. The Waterfall method, which entails requirements analysis, planning, implementation, and system testing, was used to create the website during this internship program. The website's database technology and programming languages were MySQL, PHP, HTML, and CSS. This helps to increase the institution's visibility in the digital age by presenting information about its profile, educational programs, news, and new student registration in an organized and responsive manner.